Ikan keli as a potential bioindicator for organochlorine pesticides pollution in Malaysia / Azlina Mat Saad … [et al.] - Mat Saad, Azlina; Abdul Rashid, Mohamed Kamil; Mohd Tahir, Norhayati; Abu Hassan Asari, Fadli Fizari (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Ikan keli or catfish is very synonym among Malaysian as a delicious cuisine. At the same time, less is known about its capability in becoming a bioindicator for Organochlorine Pesticides (OCPs) pollution. This is vital since most of the publications on OCPs pollution in Malaysia have used shellfish (mollusk, clam, oyster, mussel etc.) as samples. Availability is the main key, where this species is easily found in several type of water environment including river, swamp, lake, confluent and even paddy field. Scientifically known as Clarias batrachus, this species has been used as a bioindicator to investigate organochlorine pesticides (OCPs) groups namely DDTs, BHCs and Cyclodienes. In this study, samples have been selected from two different seasons which are monsoon and inter monsoon. Using Gas Chromatography Electron Capture Detector (GC-ECD), significant level of OCPs contamination has been detected. This result is similarly in range with other studies that used shellfish as their samples. From commercial perspective, this species can be reared in industrial water treatment pond. Low in maintenance cost and its resistant characteristic may assist industry in identifying their pollution level and looking for long term improvement. This will at the end contributing for better pollution management and sustainable development in Malaysia.